AL-MASKAN AL-AWWAL LI AL-INSĀN AL-AWWAL NAẒRAH FĪ AL-KUTUB AL-SAMĀWIYYAH - Jijakli, Salam Mohd. Bishr; Istanbouli, Mohamad Jalal (Islam Futura, 2024)
The Holy Books addressed the story of the first man through all of its phases; creation, living in Paradise as the first home and settling in the earth as the second and temporal one. This paper analyzes the related texts in the Holy Books, due to their importance as sources that tell this part of the humankind’s story, in addition to their religious reliability for their believers, to answer this question: What are the characteristics of the ideal house? The research follows the comparative descriptive approach by extracting the characteristics of the man’s first home from the religious texts. Then, measuring their fulfillment of the elements of architecture and the humans’ needs while comparing between the versions of the Holy Qur’an and the Holy Book. The importance of this research lies in the usage of the religious stories in connection with housing concepts and theories of architecture. The paper has accomplished conclusions and recommendations that highlight the importance of balancing the utilitarian and practical aspects with the psychological and emotional comfort while designing a home.